EVALUASI TATA KELOLA LAYANAN AKADEMIK DIGITAL UNISBANK: COBIT 2019 DOMAIN APO07 DSS02 - Sutan Sutan Cahaqiya; Agus Prasetyo Utomo (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2026)
Digital academic services at Universitas Stikubank (UNISBANK) Semarang still face obstacles regarding the high frequency of service disruptions, necessitating a systematic evaluation of IT governance. This study aims to evaluate the capability levels of the APO07 (Managed Human Resources) and DSS02 (Managed Service Requests and Incidents) domains using COBIT 2019. A quantitative descriptive method was employed using a Process Assessment Model (PAM)-based questionnaire administered to 43 respondents. The determination of capability levels is based on the adaptation of mean scores of respondent perceptions regarding process attributes, representing a questionnaire-based evaluation rather than a formal evidence audit. The results indicate that APO07 and DSS02 achieved Level 3 (Established) with average scores of 3.80 and 3.82, and gaps of 0.20 and 0.18, respectively, towards the Level 4 target. The main weaknesses were identified in workload management (APO07.05) and incident classification (DSS02.01). This study recommends improving data-driven management through quantitative performance measurements such as MTTR and ticket automation to achieve more predictable service stability.